Sosialisasi Model PJBL dalam peningkatan motivasi Siswa SMP Negeri 1 Angkola Barat Tahun Pelajaran 2024-2025 - Elnila Caniago; Fita Delia Gultom; Erni Rawati Sibuea (Jurnal Transformasi Pendidikan Indonesia, 2025)
Education is the basis of student learning that goes through in achieving learning success. In the world of education, much has been done by teachers to change knowledge which is always monotonous and boring for students. Learning using learning techniques that only use lecture learning techniques makes students become bored and even do not understand the learning material that has been presented by the teacher. Learning that has one direction will only focus on learning for students. This will result in teachers without knowing the direction and goals of learning. Using strategies that actively involve students is expected to create better enthusiasm or motivation for learning.  The service carried out at SMP Negeri 1 Angkola Barat is expected to provide knowledge in advancing the world of education, especially teachers in carrying out teaching activities. By implementing learning using the Project Based Learning (PjBL) model at SMP Negeri 1 Angkola Barat, it is hoped that teachers will be able to provide new knowledge and innovation for teachers in improving student learning and student learning outcome